Diet Drives Differences in Reproductive Synchrony in Two Sympatric Mountain Ungulates in the Himalaya - Srivastava, Tanushree; Kumar, Ajith; Kumar, Vinod; Umapathy, Govindhaswamy (Frontiers in Ecology and Evolution, 2021)
Ungulates in higher latitudes and altitudes experience sharp seasonal changes in forage abundance and quality. In response, ungulates show varying degrees of synchrony in reproduction. Diet type has been hypothesized to be a determinant of differences in reproductive synchrony. Analyses at global scales using proxies of plant phenology such as climate, latitude and Normalized Difference Vegetation Index (NDVI) have found no evidence in support because such proxies do not capture differences in phenology among plant taxa at local scales. We compared seasonal variations in diet quality with reproductive synchrony in the Himalayan musk deer (Moschus chrysogaster), a browser, and the Himalayan goral (Naemorhedus goral), a grazer, in mid-altitude Himalaya. We also compared seasonal variations in physiological stress using fecal glucocorticoid metabolite (FGM). We identified different stages of female reproductive cycle using fecal concentrations of metabolites of estradiol, pregnanediol-3-glucuronide (PdG) and testosterone and used fecal crude protein (CP) as an indicator of diet quality. In musk deer, fecal estradiol and PdG concentrations showed a dispersed estrous and parturition, respectively. Goral had a more synchronized estrous and parturition. Estrous cycles in both species occurred when diet quality was poor, but parturition occurred when diet quality was high. Greater seasonality in reproduction in goral is driven by sharp phenological changes in graminoids on which it feeds, compared to slow changes in browse on which musk deer feeds. Thus, we show that diet type drives the differences in reproductive synchrony in these two sympatric species. Spring and summer with highest diet quality were times of highest stress in both the ungulates.We hypothesize predation pressure from feral dogs and resource competition with livestock as plausible explanations for this, which need to be tested in future. Our findings also highlight the need for studying relationships among plant phenology, diet type and reproductive biology of ungulates at local scales if we are to understand species responses to global phenomena such as climate change.